Yield potential of upland rice varieties under reproductive-stage drought and optimal water regimes in Nigeria - Anyaoha, C.; Fofana, M.; Gracen, V.; Tongoona, P.B.; Blay, E.; Semon, M.; Popoola, B. (Cambridge University Press, 2018)
The goal of most rice improvement programs is the enhancement of farmers' yield using less land and limited water. This study evaluated 77 upland rice genotypes under optimal upland growing conditions in the field and ranked the genotypes using base indices. Subsequently, eighteen cultivars selected from the field trial were screened under drought in rainout-shelter conditions. The traits evaluated for index selection were yield, days to flowering, plant height, number of panicles and filled grains. Under field conditions, based on the sum of economic weight assigned to five traits used to compute the selection index, IR 68704-145-1-1-B and IR 63380-16 were the best genotypes. In the rainout-shelter experiment, Ofada 2 (508 gm−2) had the highest grain yield under non-stress conditions while ITA 117 (152.38 gm−2) had the highest grain yield under drought stress. The base index was efficient for selecting superior genotypes with the best combination for all the traits considered. Susceptibility to drought stress of the landraces leads to poor grain yield.